Spanish voseo verb typology in a five steps algorithm - Vázquez-Larruscaín, Miguel (Borealis – An International Journal of Hispanic Linguistics, 2022)
Abstract. This paper sets forth an algorithm which can recognize any type of conjugation of the Spanish voseo varieties, based on a parametric analysis of its morphological typology. The algorithm is built as a sequence of a minimum of two and a maximum of five operations, or steps. Both the linear arrangement of the steps and the content of the queries are based on an implicit theory of the relative markedness or complexity of each variant, which is also based on the parametric analysis of the typology. Thus, assessing the speed and efficiency of the algorithm becomes an indirect measure of the underlying analysis. The algorithm also invites to speculate about how the variable data relates to the way it is acquired or learned.